Training and formation of the Anaemia Response Youth Groups (KRETA) in the vocational and senior high schools of the Muhammadiyah Pringsewu - Cynthia Puspariny; Dzul Istiqomah Hasyim; Yeti Septiasari (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
The background of this activity is due to the high prevalence of anaemia in adolescents at 23.9%, which is divided into the prevalence of anaemia in women aged 5-14 years by 26.4% and in women aged 15-25 years by 18.4%. The aim was to solve the problem of high anaemia in Muhammadiyah Pringsewu vocational and high schools. Methods in this activity with Preparation, Implementation and Evaluation. The results of the activity, based on knowledge there is an increase in knowledge of adolescents participating in KRETA, an increase in Hemoglobin levels in KRETA participants, an increase in the ability to identify anaemia problems and counselling to overcome anaemia in KRETA participants. So it can be concluded that the activity was achieved and the formation of KRETA and it is hoped that there will be more similar activities with a wider range of schools.